Symptoms compatible with long COVID in an Italian pediatric cohort of Tourette patients with and without SARS‑CoV‑2 infection: a short-term follow-up assessment - Adriana Prato; Angela Maria Salerno; Federica Saia; Nicoletta Maugeri; Alice Zanini; Miriam Scerbo; Rita Barone; Renata Rizzo (BMC, 2023)
Abstract Background Tourette Syndrome (TS) is a childhood-onset neurodevelopmental disorder with a worldwide prevalence of about 0.3-1% of the population. During the pandemic caused by SARS-CoV-2 infection, the impact on the mental health of children and adolescents was very important. The persistence of symptoms in the post-acute phase of the disease has been termed Long COVID. The neuropsychiatric symptoms seem to be the most common impairment in children and adolescents with long COVID. Objectives Considering the impact of pandemic on mental health, in this study we analyzed the long-term effects of SARS-CoV-2 infection in children and adolescents affected by TS. Methods We conducted an online questionnaire covering socio-demographic and clinical data among 158 patients affected by TS or chronic tic disorders (CTD), of which 78 participants reported a positive SARS-CoV-2 infection. Data were collected to investigate tic severity and both the comorbidities, as well as lockdown-related changes to daily life activities and, in case of infection of SARS-CoV-2, possible symptoms of acute infection and long COVID. Markers of systemic inflammation including C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), ferritin, iron, electrolytes, white blood cell counts, platelet cell counts levels, markers of liver, kidney and thyroid function were analyzed. First, all patients were screened with the Schedule for affective disorders and Schizophrenia for School age children-present and lifetime (Kiddie-SADS-PL) to rule out primary psychiatric disorders considered as criteria of exclusion. Then, all patients were clinically assessed at baseline (T0), and after three months (T1) through the administration of Yale Global Tic Severity Rating Scale (YGTSS), Multidimensional Anxiety Scale for Children (MASC), Child Depression Inventory (CDI) and Child Behavior Checklist (CBCL). Results Among the cohort of TS patients that contracted SARS-CoV-2 infection, 84.6% (n = 66) experienced any acute symptoms, and long COVID symptoms occurred in 38.5% (n = 30). A worsening of clinical symptoms of tics and eventually associated comorbidities occurred in 34.6% (n = 27) of TS patients that contracted SARS-CoV-2 infection. TS patients with or without SARS-CoV-2 infection showed an increase in the severity of tics and also behavioral, depressive and anxious symptoms. Instead, this increase was more evident in patients who contracted the infection than in patients who did not contract it. Conclusions SARS-CoV-2 infection may have a role in the increase of tics and associated comorbidities in TS patients. Despite of these preliminary results, further investigations are necessary to improve knowledge about the acute and long-term impact of SARS-CoV-2 in TS patients.